Empowerment in the Lifelong Learning Perspective. Example from the “ICT Guides” Project - Renata Góralska; Joanna Leek (Rocznik Andragogiczny, 2018)
The paradigmatic change in adult education that took place in the 1990s, involving “a shift from teaching towards learning”, resulted not only in deeper reflection of andragogists on the epistemological issues concerning the specific character and conditions of adult learning, but also in the redefinition of andragogic notions including the title category of empowerment. Another consequence of this change is a different attitude towards the educational activity of adults, an example of which is the international educational project “ICT-Guides” described in the article. The first part of the article analyzes the concept of lifelong learning and characterizes empowerment, which provides the theoretical context for further deliberations. Then, the assumptions of the “ICT-Guides” project are presented. The project shows a new way of determining educational tasks and organizing educational work in the context of lifelong learning. The “ICT-Guides” project is also an example of a good practice serving empowering functions.